Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1136/jcp.2003.007641
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biology of squamous cell carcinoma of the head and neck

Abstract: Squamous cell carcinoma of the head and neck (HNSCC) is a heterogeneous but largely preventable disease with complex molecular abnormalities. It arises from a premalignant progenitor followed by outgrowth of clonal populations associated with cumulative genetic alterations and phenotypic progression to invasive malignancy. These genetic alterations result in inactivation of multiple tumour suppressor genes and activation of proto-oncogenes, including p16ink4A, p53, cyclin D1, p14ARF,FHIT,RASSF1A, epidermal gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
196
0
8

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(213 citation statements)
references
References 93 publications
9
196
0
8
Order By: Relevance
“…Study of the natural history of oral cancer and precancer should identify critical stages that can be used to develop preventive strategies or for early detection that may improve the survival rate associated with oral cancer. We attempted to study the role of FHIT in a multistep malignant transformation model of oral carcinogenesis (42). Our results showed that FHIT downregulation is an early frequent event in oral carcinogenesis and may provide a predictor marker for disease progression and outcome alongside other conventional clinicopathologic and molecular markers that are in use.…”
Section: Discussionmentioning
confidence: 99%
“…Study of the natural history of oral cancer and precancer should identify critical stages that can be used to develop preventive strategies or for early detection that may improve the survival rate associated with oral cancer. We attempted to study the role of FHIT in a multistep malignant transformation model of oral carcinogenesis (42). Our results showed that FHIT downregulation is an early frequent event in oral carcinogenesis and may provide a predictor marker for disease progression and outcome alongside other conventional clinicopathologic and molecular markers that are in use.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that genetic variation modulates cancer risk associated with environmental risk factors and that genetic variation may serve as a biomarker to identify individuals at risk of developing cancer [2]. Cumulative genetic alterations have been shown to be associated with phenotypic progression of SCCHN, resulting in inactivation of multiple tumor suppressor genes and activation of proto-oncogenes [3]. Among them, p16INK4A at chromosome 9p and RASSF1A at chromosome 3p are two major tumor suppressor genes epigenetically inactivated at the early stage from normal mucosa to dysplasia [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…All of these treatment modalities have undergone improvements over the last several decades and have led to improvements in outcomes for some types of HNSCC (for example, advanced laryngeal and pharyngeal carcinoma; ref. 3). Despite these advances, the 5-year survival rate for HNSCC as a whole remains at ∼50% (2).…”
Section: Introductionmentioning
confidence: 99%